2007
DOI: 10.1161/atvbaha.107.142182
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Role for eNOS-Derived Reactive Oxygen Species in Atherosclerosis Progression

Abstract: Objective-When the availability of tetrahydrobiopterin (BH4) is deficient, endothelial nitric oxide synthase (eNOS) produces superoxide rather than NO (uncoupled eNOS). We have shown that the atherosclerotic lesion size was augmented in apolipoprotein E-deficient (ApoE-KO) mice overexpressing eNOS because of the enhanced superoxide production. In this study, we addressed the specific importance of uncoupled eNOS in atherosclerosis, and the potential mechanistic role for specific versus nonspecific antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 30 publications
3
59
0
2
Order By: Relevance
“…PE enhanced the cGMP level significantly in WT mice but not apoE-KO mice (Fig. 8B), suggesting that the NO/cGMP signaling mechanism compensatively increased in aortas from apoE-KO mice in early atherosclerosis, as reported previously 45,46) . The reason why PE does not raise the cGMP level of aortas from apoE-KO mice so much is unclear.…”
Section: Discussionsupporting
confidence: 86%
“…PE enhanced the cGMP level significantly in WT mice but not apoE-KO mice (Fig. 8B), suggesting that the NO/cGMP signaling mechanism compensatively increased in aortas from apoE-KO mice in early atherosclerosis, as reported previously 45,46) . The reason why PE does not raise the cGMP level of aortas from apoE-KO mice so much is unclear.…”
Section: Discussionsupporting
confidence: 86%
“…Based on these findings, GTPCH1 is reported to be a potential and rational target to augment endothelial BH4 in reversing eNOS activity in endothelial dysfunctional states. Recently, Takaya et al [42] showed that augmenting BH4 levels in the endothelium by GTPCH1 overexpression reduces atherosclerosis in apoE KO/eNOS Tg mice and is associated with a reduction in O 2 -from uncoupled eNOS. In the present study, we focused on the effects of CRP on intracellular BH4 levels.…”
Section: Discussionmentioning
confidence: 99%
“…93,94 Recent clinical data also indicates that variants of GTP cyclohydrolase I are governing NO production, autonomic activity and even cardiovascular risk. 95 With respect to hypertension, an important study by Du et al 96 showed that increased oxidative stress due to eNOS uncoupling may directly affect blood pressure.…”
Section: Ros Sources In Hypertension Nadph Oxidasesmentioning
confidence: 99%